Matrix and interface cracking in cross-ply composite structural battery under combined electrochemical and mechanical loading. (20th January 2020) - Xu, Johanna; Varna, Janis
Abstract: In this paper propagation of matrix cracks and debonds at the coating/matrix interface in the 90°-layer of a cross-ply structural composite battery are studied numerically. The structural composite battery consists of micro-battery units, made of a solid electrolyte coated carbon fiber embedded in an electrochemically active polymer matrix. During charging the fiber swells and the matrix shrinks leading to high stresses on the fiber/matrix scale and to anisotropic free expansion of the composite ply. Two load cases are considered, pure electrochemical load (intercalation) and combined electrochemical and thermomechanical load. Energy release rates (ERR) of radial matrix cracks along two potential propagation paths are calculated using 2-D finite element models of the transverse plane in a cross-ply laminate with a square packing of fibers in the 90°-ply and using homogenized 0°-ply. Results show that the matrix crack growth towards the nearest fiber is unstable, and that the debond crack growth is in mixed mode. For a cross-ply structural battery composite the sequence of macro-scale crack forming events differs from a conventional cross-ply composite, as well as for a UD composite battery laminate. The most likely course of failure events in a cross-ply laminate are: 1) vertical radial matrix crack initiation and unstable growth; 2) debond is initiated at certain length of the matrix crack.